Desain Pengembangan Modul Pembelajaran Berbasis Pendekatan Saintifik pada Mata Pelajaran Otomatisasi Tata Kelola Sarana dan Prasarana Kelas XI SMKN Ngraho Bojonegoro - Ridha Wahyuningtyas; Novi Trisnawati (Universitas Negeri Surabaya, 2021)
The purpose of this study was to develop a Scientific-based module in the subject of Automation of Facilities and Infrastructure Management for Class 11 of SMK Negeri Ngraho Bojonegoro. This study uses a 4-D (Four D) development method with designs such as roll definitions, design, development design, development, and development, and this study uses XI OTKP research at SMK Negeri Ngraho. This research uses research and development (R&D) which means